First description of the female of Coeliccia furcata Hämäläinen, 1986, with descriptive notes on males from Yunnan, China (Odonata: Zygoptera: Platycnemididae) - Dow, Rory A.; Zhang, Hao-Miao (Zootaxa, 2021)
Coeliccia furcata Hämäläinen, 1986, an atypical species of Coeliccia Kirby, 1890 with bifurcated male cerci, had been known solely from the holotype male collected in Myanmar in 1938. In recent years the species has been rediscovered in Yunnan, China. The first description of the female is given, along with descriptive notes on the male and illustrations of both sexes, including fresh images of the holotype. Another of the unusual features of C. furcata is the extremely simple form of its penile organ, this is discussed and compared with other species from mainland Asia and Japan currently placed in Coeliccia and with a simple penile organ.